Language Styles in the Movie Luca (2021): Sociolinguistics Study - Vika Octavia Larasati; Ervina CM Simatupang (Budapest International Research and Critics University, 2022)
The title of this study is Language Styles in the Movie Luca (2021): Sociolinguistic Study. Accordingly, this study aims to analyze the data based on sociolinguistic studies to better comprehend language usage related to the different types of styles and functions of language. The theories employed to analyze the types of language styles are from Martin Joo (1976), whilst the theory from Roman Jakobson (1980) is used to analyze the language function. The method used in carrying out the study is descriptive qualitative analysis. Based on the findings of the research, the most occurring types of language style is consultative style with 26%, casual style with 25%, formal style with 21%, frozen style and intimate style with 14%. Moreover, there are six categories of functions in utilizing language style that are present in the film including emotive, referential, and phatic function of which is most dominating.